Процедуры оптимизации распределения информационных потоков в агентных мультисервисных сетях - Безрук, Валерий Михайлович; Буханько, А. Н.; Дуравкин, Е. В. (Eastern-European Journal of Enterprise Technologies, 2014)
This article is represented a general characteristic of the decentralized control systems on the basis of operating agents. There are resulted some management procedures by information streams in multiservice networks and results of their application